1997
DOI: 10.1177/00220345970760091301
|View full text |Cite
|
Sign up to set email alerts
|

Oral Hygiene Habits of 11-year-old Schoolchildren in 22 European Countries and Canada in 1993/1994

Abstract: This study is part of the Cross-National Survey on Health Behaviour in School-aged Children--a WHO Collaborative Study, which started in 1982. The aim of the study was to describe the oral hygiene habits (toothbrushing and flossing) of 11-year-old schoolchildren in 22 European countries (Austria, Belgium, the Czech Republic, Denmark, Estonia, FInland, France, Germany, Greenland, Hungary, Israel, Latvia, Lithuania, Northern Ireland, Norway, Poland, Russia, Scotland, the Slovak Republic, Spain, Sweden, and Wales… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
100
4
9

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(131 citation statements)
references
References 13 publications
18
100
4
9
Order By: Relevance
“…In Norway, Austria, Germany, Denmark, and Sweden, 73-83% of children as young as 11 years old brushed more often than once a day [32]. Females at the HSC followed the recommended toothbrushing frequency more often than males, which is consistent with results from studies conducted in other countries [3,[32][33][34][35].…”
Section: Discussionsupporting
confidence: 82%
“…In Norway, Austria, Germany, Denmark, and Sweden, 73-83% of children as young as 11 years old brushed more often than once a day [32]. Females at the HSC followed the recommended toothbrushing frequency more often than males, which is consistent with results from studies conducted in other countries [3,[32][33][34][35].…”
Section: Discussionsupporting
confidence: 82%
“…Many published studies have considered frequency of toothbrushing both in the UK and in other European countries. [1][2][3][4][5][6][7] In the UK Child Dental Health Survey, O'Brien 4 found that 13% of 15-year-olds brushed their teeth three or more times daily, 67% twice daily, 17% once daily and 3% less often than daily; these finding are somewhat higher than in the current study. The comparable figures were 12% brushing three times daily, 60% twice daily and 27% brushed once per day or less.…”
Section: Discussionmentioning
confidence: 62%
“…However, Honkala et al 6 surveyed 11-13 and 15-year-old adolescents in 11 European countries and reported the highest brushing frequency in Sweden; 98% of these children brushed daily compared with the lowest levels in Spain, where only 68% of children brushed daily. Kuusela et al 7 described the oral hygiene habits of 11-year-old schoolchildren in 22 European countries and Canada. This was part of a WHO Collaborative Study based on data collected during 1993-1994.…”
mentioning
confidence: 99%
“…Cabe señalar que estas diferencias no fueron estadística-mente significativas (prueba ANOVA para muestras repetidas (p=0,163), sin embargo, se menciona esto porque se podría deducir que las mujeres aprovecharon mejor las técnicas de higiene oral impartidas durante el PESOS. Así mismo, estudios similares muestran mejores resultados en adolescentes de sexo femenino, con diferencias estadísti-camente significativas (5,17,18).…”
Section: Discussionunclassified